2017
DOI: 10.1016/j.fsi.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera enhances the innate immune response of pacu (Piaractus mesopotamicus) after transport stress and combined heat killed Aeromonas hydrophila infection

Abstract: In this study, pacu (Piaractus mesopotamicus) were fed with diets containing Aloe vera for 10 days prior to transport stress and infection with heat killed Aeromonas hydrophila. A. vera is popular around the world due to its medicinal properties, including immunostimulatory effects which was observed in this study. The results show that transport causes immunosuppression, an effect that was prevented by A. vera. Specifically, A. vera prevented reductions of both leukocyte respiratory burst and hemolytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 88 publications
2
27
0
1
Order By: Relevance
“…Gabriel et al (2015a) reported the same in a GIFT strain O. niloticus fed 100% A. vera extracts. In addition, improved innate immune response after dietary A. vera supplementation was reported in matrinxa, Brycon amazonicus (Zanuzzo et al 2015b); whiteleg shrimp, Litopenaeus vannamei (Trejo-Flores et al 2016); and pacu, Piaractus mesopotamicus (Zanuzzo et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Gabriel et al (2015a) reported the same in a GIFT strain O. niloticus fed 100% A. vera extracts. In addition, improved innate immune response after dietary A. vera supplementation was reported in matrinxa, Brycon amazonicus (Zanuzzo et al 2015b); whiteleg shrimp, Litopenaeus vannamei (Trejo-Flores et al 2016); and pacu, Piaractus mesopotamicus (Zanuzzo et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Zanuzzo et al . () administered one of four diets (0%, 0.5%, 1% or 2% A. vera ) for 10 days prior to a 4 h transport of juvenile pacu ( Piaractus mesopotamicus, Holmberg 1887). Immediately following transport, the pacu were divided into three sub‐groups: a noninjected control group, a buffer injected group and a group injected with inactivated Aeromonas hydrophila (Chester 1901) to stimulate their immune system.…”
Section: Can We Prepare Fish For Transportation Stress?mentioning
confidence: 99%
“…One study looked at A. vera as a dietary supplement prior to transport (Zanuzzo et al . ; see above) and an additional study by the same group used A. vera in the water during transport of fish. Zanuzzo et al .…”
Section: The Use Of Additives During Transportmentioning
confidence: 99%
See 2 more Smart Citations